ANALISIS YURIDIS PRINSIP KEMANDIRIAN DAN KERAHASIAAN PASAL 16 AYAT (1) HURUF A DAN HURUF F BERKAITAN DENGAN PASAL 20 UU NO. 2 TAHUN 2014 TENTANG PERUBAHAN ATAS UU NO. 30 TAHUN 2004 TENTANG JABATAN NOTARIS - VALENTINA CANDORA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Notaris Dr. Henry Sinaga, SH, MKn2.  Notaris Dr. Suprayitno, SH, MKn3.  Notaris Dr. Tony, SH, MKn In doing his job, a Notary is required to adhere to the regulation in Article 16,paragraph 1, letter a and letter f of Law No. 2/2004 on the amendment to Law No. 30/2004on Notarial Position which states that a Notary, in doing his job, will be independent andimpartial, and confidential concerning the content of the deeds and of any informationrelated to the deeds he makes. However, Article 20 of Law No. 2/2004 on the Amendmenton Law No. 30/2004 on Notarial Position states that a Notary can establish civilassociation. He can have an office collectively, doing with the other Notaries in the samebuilding/floor, using the same facilities. The research problems are how a Notary canguarantee confidentiality in doing his job in notarial civil association, how a Notary canapply the principle of independency in doing his job in the form of notarial civil association,and how about the sanction imposed on a Notary in notarial civil association who divulgesconfidentiality of a deed. The research used descriptive analytic and juridical normativemethod. The data were gathered by conducting library research and documentary studyand analyzed qualitatively while conclusion was drawn deductively. Primary data wereobtained from interviews, and secondary data were obtained from primary, secondary, andtertiary legal materials. A Notary in a notarial civil association can guaranteeconfidentiality and does his job as a Notary in general who has professional confidentiality.He can also apply the principle of independency, working by himself in his own room andkeeping his own protocols. However, criminal, civil, and administrative sanction willimposed on him if he divulges confidentiality.Keywords: Notarial Civil Association; Principle of Independency andConfidentiality